Forgotten fatalities: British military, mining and maritime accidents since 1900. (20th August 2021) - Roberts, S E; Carter, T; Smith, H D; John, A; Williams, J G
Abstract: Background: Comparative long-term trends in fatal accident rates in the UK's most hazardous occupations have not been reported. Aims: To compare trends in fatal accident rates in six of the most hazardous occupations (the three armed forces, merchant shipping, sea fishing and coal mining) and the general British workforce during peacetime years since 1900. Methods: Examinations of annual mortality reports, returns, inquiry files and statistics. The main outcome measure was the fatal accident rate per 100 000 population employed. Results: These six occupations accounted for 40% of all fatal accidents in the British workforce. Fatal accident rates were highest in merchant shipping to 1914 (400–600 per 100 000) and in the Royal Air Force and sea fishing by the early 1920s (around 300 per 100 000). Since the 1950s sea fishing has remained the most hazardous occupation (50–200). Widespread reductions in fatal accident rates for each occupation have been greatest in recent years in the three armed forces and merchant shipping. Compared with the general workforce, relative risks of fatalities have increased in recent decades in all these occupations except shipping. Conclusions: All six occupations still have high fatal accident rates. The greatly increased fatalities in sea fishing generally and in the Royal Air Force during its early years reflect, for different reasons, cultures of extreme risk-taking in these two sectors. Reductions in fatality rates in the armed forces over the last 20 years are due largely to decreases in land transport accidents.